A Comparative Analysis of CRISPR-Cas9, Base Editing and Prime Editing Technologies for Precision Gene Therapy in Cardiac Disease Applications - Salah Uddin; Munir, Iffat; Shah, Syeda Hina; Khalid, Afshan; Ali, Sana Barkat; Faisal, Mohammad Rayyan (Indus Journal of Bioscience Research, 2025)
This study provides a comparative analysis of CRISPR-Cas9, base editing, and prime editing technologies based on their potential applications in precision gene therapy for genetic heart diseases. The primary objective was to compare the efficiency, accuracy, and safety of these technologies in editing cardiomyocyte genes and their implications for the treatment of cardiac diseases. Employing induced pluripotent stem cell (iPSC)-derived cardiomyocytes, we compared editing efficiency, off-target mutations, cell viability, electrophysiological properties, and protein expression following gene editing. The results indicated that base editing exhibited the highest editing efficiency (92%) and protein expression (91%), while prime editing exhibited the best performance in minimizing off-target mutations and maintaining a higher cell viability (92%) compared to CRISPR-Cas9 (85% and 90%, respectively). However, CRISPR-Cas9 exhibited a slightly longer action potential duration in cardiomyocytes. Statistical analyses conducted using one-way ANOVA revealed significant differences between some technologies in editing efficiency, cell viability, and electrophysiological properties, but no significant differences were found for off-target mutations or gene correction accuracy. These findings suggest that while base editing and prime editing possess different advantages, the selection of technology will be based on specific therapeutic requirements, with base editing being more efficient and prime editing possessing better precision and safety profiles. The study suggests the potential of these new gene-editing technologies to overcome the limitations of traditional CRISPR-Cas9 in the treatment of genetic cardiac diseases, thereby opening new avenues for precision medicine.